Overview of the Development of the Korean Exposure Factors Handbook - Jae-Yeon Jang; Soo-Nam Jo; So-Yeon Kim; Hyung-Nam Myung (Korean Society for Preventive Medicine, 2014)
A set of exposure factors that reflects the characteristics of individual behavior capable of influencing exposure is essential for risk and exposure assessment. In 2007, the Korean Exposure Factors Handbook was, therefore, issued, driven by the need to develop reliable exposure factors representing the Korean population. The purpose of this study was to overview the development process of the Korean Exposure Factors Handbook and major recommended exposure values for the Korean population to allow information exchanges and comparison of recommended values among nations. The researchers reviewed the domestic data that could be used in the development of exposure factors, confirmed a knowledge gap, and set a priority of development by phases. A methodology to measure exposure factors was established to develop measuring techniques and test their validity. Data were processed or a survey was conducted according to the availability of data. The study thus produced recommended values for 24 exposure factors grouped by general exposure factors, food ingestion factors, and activity factors by setting up a database of exposure factors and carrying out statistical analysis. The study has significantly contributed to reducing the potential uncertainty of the risk and exposure assessment derived by the application of foreign data or research findings lacking representativeness or grounds by developing a set of exposure factors reflecting the characteristics of the Korean people. It will be necessary to conduct revisions in light of the changing statistical values of national data and the exposure factors based on Korean characteristics.